2022
DOI: 10.31822/jomat.2022-7-1-67
|View full text |Cite
|
Sign up to set email alerts
|

A bibliometric analysis of food studies: Evidence from British Food Journal

Abstract: The objective of the current study is to overview the British Food Journal publications from 2010 to 2020. To address our purpose, bibliometric and visualization analyses were used. Firstly, a total of 1892 documents published from 2010 to 2020 in the British Food Journal (BFJ) was obtained from the Web of Science database (WoS). Then, the analyses were made by running VOS viewer software. In the process of analyzing data, we have principally considered some bibliometric indicators such as the number of annual… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 69 publications
0
2
0
Order By: Relevance
“…In the field of tourism, studies on food safety on various topics are observed. In this context, food security has been examined by bibliometric analysis (Lakner et al, 2021;Şahin, 2021;Teyin, 2021;Shen et al, 2021;Liu et al, 2023); Tarulevicz & Ooi, 2022;Öğretmenoğlu et al, 2022), its impact on tourism (MacLaurin, 2004;Bellia et al, 2016;Dolmacı & Bulgan, 2018;Lee et al, 2019;Tarulevicz & Ooi, 2022), its impact on consumer perception of eating out (Knight et al, 2009;Lee et al, 2012;Bai et al, 2019;Cha & Borchgrevink, 2019), determining the level of knowledge of the personnel working in food and beverage establishments (Kızılcık & Giritoğlu, 2016;Ayaz & Aydın, 2017;Souza et al, 2018), and training of the food department employees in hotel establishments (Gomes et al, 2014).…”
Section: Extended Summarymentioning
confidence: 99%
“…In the field of tourism, studies on food safety on various topics are observed. In this context, food security has been examined by bibliometric analysis (Lakner et al, 2021;Şahin, 2021;Teyin, 2021;Shen et al, 2021;Liu et al, 2023); Tarulevicz & Ooi, 2022;Öğretmenoğlu et al, 2022), its impact on tourism (MacLaurin, 2004;Bellia et al, 2016;Dolmacı & Bulgan, 2018;Lee et al, 2019;Tarulevicz & Ooi, 2022), its impact on consumer perception of eating out (Knight et al, 2009;Lee et al, 2012;Bai et al, 2019;Cha & Borchgrevink, 2019), determining the level of knowledge of the personnel working in food and beverage establishments (Kızılcık & Giritoğlu, 2016;Ayaz & Aydın, 2017;Souza et al, 2018), and training of the food department employees in hotel establishments (Gomes et al, 2014).…”
Section: Extended Summarymentioning
confidence: 99%
“…, 2020). In addition, it can contribute new ideas to researchers who study the development and use of food packaging (Öğretmenoğlu et al. , 2021).…”
Section: Introductionmentioning
confidence: 99%
“…Nicel bir analiz yöntemi olan bibliyometride, dergilerde yayınlanan makaleler ve atıflar istatistiksel olarak analiz edilir. Ayrıca kitaplar, tezler, raporlar ve patentler bibliyometrik analizin unsurları olarak kabul edilse de bilimsel makaleler bibliyometrinin ana unsurunu oluşturmaktadır ( [3], [4], [5], [6]…”
Section: Introductionunclassified